Education on the Benefits of Red Ginger (Zingiber officinale) to Overcome Menstrual Pain in Adolescent Girls in Gembleb Trenggalek: Edukasi Manfaat Jahe Merah (Zingiber officinale) Untuk Mengatasi Nyeri Haid Pada Remaja Putri di Dusun Gembleb Trenggalek - Saristiana, Yuneka; Prasetyawan, Fendy; Salmasfattah, Novyananda; Savitri, Lisa; Megasari, Elly; Indrayanti, Dian (PELITA NUSA TENGGARA, 2025)
This community service program aimed to educate adolescent girls in Dusun Gembleb, Trenggalek, on the benefits of red ginger (Zingiber officinale) as a natural remedy for alleviating menstrual pain. Menstrual pain, or dysmenorrhea, is a common health issue affecting a significant number of adolescent girls, often leading to disruption in daily activities. While conventional pain relief medications are commonly used, their long-term side effects can be detrimental. Red ginger, known for its anti-inflammatory and analgesic properties, offers a safer alternative. The program, held on May 3, 2025, at the Gembleb Village Office, included educational sessions on the medicinal properties of red ginger, practical demonstrations on how to prepare red ginger tea, and discussions on its health benefits. The results showed a significant improvement in participants' understanding of red ginger's therapeutic effects, as evidenced by pre-test and post-test comparisons. This initiative successfully raised awareness about alternative treatments and empowered the community to utilize locally available resources for health improvement.